Protection of Immigrant Children and Youth at Risk: Experiences and Strategies of Social Integration in Portugal - Casquilho-Martins, I.; Matela, T. (Societies, 2021)
Over the years, social projects and programmes in Portugal have resulted in actions and outcomes to improve the integration and social inclusion of immigrant children and young people in socially vulnerable territories. This article aims to analyse the intervention experiences of teams with immigrant children and young people at risk. The developed study focused on a qualitative approach through the systematisation of measures to protect the rights of immigrant children and young people in Portugal. Semi-structured interviews were also carried out with professionals working in multidisciplinary teams intervening with immigrant children and young people. The results allow the identification of strategies and intervention methods with a positive impact on social integration supported by collaborative and participatory methodologies, but also highlight limitations such as cultural and linguistic barriers, and lack of children’s participation. Thus, it becomes fundamental to value the central role of children and young people in promoting and guaranteeing their rights.